Estimation of corrosion resistance of curing mixtures based on coal-bearing rocks from western Donbass - Kovalenko, V.; Harkusha, V. (Розробка родовищ, 2016)
Purpose. Substantiation of possible use of coal-bearing rocks as a replacement for a part of the filler in the preparation of shotcrete for lining of mine workings in the conditions of mineralized mine water. Methods. The research is based on carrying out corrosion testing of concrete specimens by dipping them into mine water. Chemical analysis of mine waters composition has been completed. A scanning microscope was used to study the state of concrete specimens microstructure. Findings. A comparative analysis was conducted to evaluate of the cement rock resistance to mineralized water, depending on the composition of the starting components for the grouting and shotcrete mixtures is carried out. The change in the chemical composition of mine water after soaking concrete specimens in it is defined. Photographs of concrete specimens microstructure after soaking in ordinary and mineralized water for 6 and 8 months are shown. Originality. Curing mixtures based on coal-bearing rocks from Western Donbass are mineralized water resistant and can act as a quality protection from aggressive water filtrationdue to the properties of rocks used as a filler. Practical implications. The results can be used for the rational choice of the composition of the concrete mixture with the replacement of filler part with mine rock. That will enhance the long-term stability of the mine working lined by these compositions.